(untitled) (Revista Direitos Humanos e Democracia, 2025)
This paper aims to analyze the dialectical tension between the instituted dimension and the instituting dimension of human rights and the role of the Inter-American Human Rights System - IAHRS in the realization of rights. This work explores the foundations of human rights and reflects on the maintenance of relations of domination in society, despite the validity of normative instruments that should promote emancipation. The question of the purpose of human rights is relevant in social and institutional spheres, which may come into tension and reveal deficits between the discourses of the instituted dimension and the instituting dimension. In this respect, the objections of individuals or groups, who suffer from political, social, economic and legal injustices, deserve to be heard by institutions so that structures can be built that recognize the dignity of the population in all their ways of being and living. People’s involvement in the processes of attributing meaning to human rights can provide new horizons, as it allows mutual learning between the two spheres of human rights. Thus, the IAHRS plays an important role in resolving cases of neglected human rights violations at the domestic level, which are only analyzed after the victims struggle for recognition. The Case of González and Others (Campo Algodoeiro) vs. Mexico exemplifies the dialectical relationship between the instituting and established dimensions of human rights, in which the testimonies of victims’ families contributed to the IAHRS incorporating the concept of femicide and exploring the case from a gender perspective in a way that was unprecedented in its jurisprudence.